Is routine dissection of the station 9 lymph nodes really necessary for primary lung cancer?. (October 2016) - Sun, Fenghao; Zhan, Cheng; Shi, Mengkun; Yang, Xiaodong; Wang, Lin; Jiang, Wei; Lin, Zongwu; Xi, Junjie; Shi, Yu; Wang, Qun
Abstract: Objectives: Mediastinal lymph node dissection is an essential component of lung cancer surgery; however, choosing mediastinal lymph nodes stations to be dissected is subjective. We carried out this research to investigate the need for dissection of station 9 lymph nodes during lung cancer surgery. Methods: Patients with primary lung cancer who underwent radical surgery between 2010 and 2014 were retrospectively reviewed. Clinical, pathologic, and prognosis data were obtained and analyzed. Results: A total number of 1397 patients were included in this research. The metastasis rate of station 9 was 3.45%, which was significantly lower than other mediastinal stations. This metastasis rate was significantly correlated with pT stage, the lobe where the tumor was located, metastasis status of intrapulmonary lymph nodes, pTNM stage, and most of the other mediastinal lymph node stations. In males or ground glass opacity (GGO) patients, the metastasis of station 9 nodes was more unlikely to occur, even though there was no statistical significance. The staging results of most patients (99.63%) would not be impaired, even if station 9 nodes were not dissected, and the prognostic analysis showed that the metastasis status of station 9 had no significant influence on survival. Conclusion: The metastasis rate of station 9 lymph nodes was significantly lower than other mediastinal stations in lung cancer patients. The metastasis status of station 9 had no significant influence on tumor staging or prognosis. Routine dissection of station 9 lymph nodes may not be necessary, especially in patients with a low T stage, upper or middle lobe tumors, or without intrapulmonary lymph node metastasis. Highlights: The metastasis rate of station 9 lymph nodes was significantly lower than other mediastinal stations in lung cancer patients. The metastasis status of station 9 had no significant influence on tumor staging or prognosis. Station 9 metastasis is significantly correlated with T stage, tumor location and intrapulmonary node metastasis.